1980
DOI: 10.1902/jop.1980.51.9.505
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Procedure for the Treatment of Localized Gingival Recession in Conjunction With Root Surface Citric Acid Conditioning

Abstract: A total of 9 teeth were treated with a free gingival graft followed by a coronally positioned flap in conjunction with conditioning of the root surface with citric acid. The grafting procedure was done 2 weeks after the subjects could perform adequate plaque control. Thirty days after grafting, a mucoperiosteal flap was raised. The root surface was thoroughly planed and conditioned with citric acid at pH 1.0, and the flap was then positioned coronally. Clinical measurements of the amount of recession, sulcus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
4

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 13 publications
1
22
0
4
Order By: Relevance
“…205'206 Articles on the use of root conditioning in conjunction with root coverage procedures are summarized in Table 7.99. [102][103]140,159464,175,180,182,185,187,188,193,196,197,201 Controlled clinical trials comparing the effect of free gingival graft procedures with and without root condition-ingis7, 193,197,201 <jid not demonstrate any beneficial clinical effect from the use of citric acid. Also controlled studies comparing the211 effect of laterally positioned flap with and without root conditioning showed no statistically significant positive effect with the use of citric acid.99 175 No controlled studies on the effect of tetracycline HCl are available.…”
Section: Root Surface Conditioningmentioning
confidence: 99%
“…205'206 Articles on the use of root conditioning in conjunction with root coverage procedures are summarized in Table 7.99. [102][103]140,159464,175,180,182,185,187,188,193,196,197,201 Controlled clinical trials comparing the effect of free gingival graft procedures with and without root condition-ingis7, 193,197,201 <jid not demonstrate any beneficial clinical effect from the use of citric acid. Also controlled studies comparing the211 effect of laterally positioned flap with and without root conditioning showed no statistically significant positive effect with the use of citric acid.99 175 No controlled studies on the effect of tetracycline HCl are available.…”
Section: Root Surface Conditioningmentioning
confidence: 99%
“…Numerous longitudinal human studies have been presented to support the efficacy and predictability of different surgical techniques that have been proposed to address this issue. 1 The proposals can be summarized as follows: palatal masticatory mucosa grafted onto the recession area (EFGG); 2-17 only a layer of connective tissue grafted onto the recession area (CTG); 10,12,15, use of the gingiva from adjacent teeth as a rotated and/or sliding pedicle flap to cover the exposed root surface (LPF); 8,44-52 moving the residual gingiva at the recession site in a coronal direction (CAF); 26,53-63 coronal positioning of previously grafted tissue (EFGG + CAF); 14,46,[64][65][66][67][68][69][70] and use of resorbable and non-resorbable membranes according to the principles of guided tissue regeneration (GTR). 28,29,33,34,37,38,[40][41][42]58,62, A careful review made it possible to summarize the descriptive statistics reported in the published clinical studies on root coverage and to compute the missing statistics from the published data whenever possible.…”
mentioning
confidence: 99%
“…One of the most widely used mucogingival procedures to achieve root coverage is the coronally advanced flap (CAF). Several authors have utilized this approach, applying the following techniques: shifting the residual gingiva (CAF) in a coronal direction [1][2][3][4][5] or using a previously placed epithelialized free gingival graft (2-stage procedure: EFGG + CAF) [6][7][8][9][10][11][12] to cover a connective tissue graft (CTG) 3,[13][14][15][16][17] or a bioabsorbable or non-resorbable membrane, according to the principles of guided tissue regeneration (GTR). 5,12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31] The reported average percent root coverage in Miller Class I and II recession defects 32 ranges from 60% 4 to 99% 2 for CAF; from 36% 11 to 74% 8 for EFGG + CAF; from 70% 16 to 98% 3 for CAF associated with CTG; and from 52% 29 to 90% 26 for CAF in combination with GTR techniques.…”
mentioning
confidence: 99%
“…One of the fundamental steps of root coverage procedures is the preliminary mechanical root surface modification (root planing), suggested by most authors for different purposes, such as smoothing irregularities and grooves of the root surface, 33 removing root caries lesions, [34][35] reducing the convexity of the root and the mesio-distal distance between periodontal spaces, [36][37] and minimizing cementum toxicity. 38 In combination with scaling and root planing, several authors suggest the use of different chemical agents, such as citric acid, 1,9,11,16,[37][38][39][40][41][42][43][44] tetracycline HCl, 2,15,30,45 fibrin glue associated with tetracycline HCl, [4][5]20 and sodium hypochlorite. 46 These agents have been used to remove the smear layer produced by root instrumentation; expose the collagen fibrils of the dentin matrix, facilitating the formation of new connective tissue attachment; 47,48 and remove cytopathic substances that inhibit human gingival fibroblast growth from infected cementum.…”
mentioning
confidence: 99%